Green Inhibition of Mild Steel Corrosion in a CO2 Saturated Saline Solution - Gomes, Elron Edgar (2015)
A Master of Science thesis in Chemical Engineering by Elron Edgar Gomes entitled, "Green Inhibition of Mild Steel Corrosion in a CO2 Saturated Saline Solution," submitted in May 2015. Thesis advisor is Dr. Taleb Ibrahim. Soft and hard copy available.